Os instrumentos para a preservação do poder e do Estado em Maquiavel - Freitas, William de Jesus Costa (Universidade do Vale do Rio dos Sinos, 2015)
In the context of Machiavelli observed the decay of Christianity, capitalism’s rise, the development of national states, where local rulers are absorbed by the strengthening of the monarchies and the increasing centralization of political institutions. Machiavelli as empirical thinker, notes the consolidation of central power in England and France, and the same is not true in their beloved city, Italy which appears to be a conglomeration of small rival city-states, disputed by the Pope, Germany, France and Spain. Dispute favoring particularism, but becomes catastrophic for the fate of the peninsula. Realize the existence of an instrumental rationality in man which leads him to seek success without caring about ethical values. This fact leads him to think of a fallen human nature by evil. In vain men, cowardly, ungrateful, envious that we must always be prepared for anything, that is, for the worst of them. Given this reality the Florentine will become the precursor of two major political theory of ideas, linked together, both expressed in his works. The first, that only the power controls the power is the only weapon that counts. The second idea is that the internal discord is inherent in free governments. In this sense Machiavelli becomes revolutionary against a tradition that stigmatized discord as “turmoil”, striving for harmony and unity. Concerned about the situation in Italy Machiavelli feels the need for a firm hand able to confront the fortune, considered by Florentine as own contingency of human actions and not manifestations of God. Also think the need for a state with central and sovereign power you have in Prince include the establishment of their acts of government as sovereign acts. Acts of the prince government, there is indeed more than the manifestation of his mastery of the art of government; Prince is the source of political power and should provide that - within their first, and in relations that this keeps with the other powers - it is your only source or at least dominates their sources. Hence, the exercise of power should make use of the necessary tools that can keep it as long as possible in power and that can guarantee state stability. Considering the above, this thesis has as purpose categorize the appropriate tools for the success of the ruler. Before however it was necessary to contextualize the author because it was a result of the events in his homeland that Machiavelli modern political thought, the power, the need of the state, the good ruler and the instruments to be used. The methodological approach started from a literature review on the topic, using primary sources (the works written by Machiavelli) and secondary sources (commentators).
Keywords: Virtu; Fortuna; Estado; Liberdade; State; Freedom; ACCNPQ::Ciências Humanas::Filosofia